Profil Norma Sosiomatematika dalam Pembelajaran Kolaboratif Materi Bentuk Aljabar Siswa Kelas VII-C SMPN 13 Mataram - M. Satria Ramanda; Sri Subarinah; Amrullah Amrullah; Laila Hayati (Griya Journal of Mathematics Education and Application, 2021)
This research aims to describe the profile of implementation mathematics learning and sociomatematic norms in collaborative learning of algebraic material topic at VII-C SMPN 13 Mataram in the 2019/2020 academic year. Indicators of sociomathematic norms in this research are based on the ability to communicate mathematics and the social skills students in collaborative learning. The kind of research this is descriptive qualitative with instruments of data collection which used are the learning device which includes RPP, LLPD, observation sheet of sociomathematic norms in collaboration activities and interview guidelines. The subjects in this study were 30 students who had a category of positive belief in collaborative activities. There are 3 categories of positive belief, namely P1, P2 and P3. P1 subject has a positive belief in collaborative activities and has the ability to solve problems independently, many as 0 people. P2 subjects who have positive beliefs about the effectiveness of collaboration and have the ability to solve problems independently but sometimes need the help of a friend or teacher, many as 28 people. P3 subjects who have positive belief in collaborative activities and do not have the ability to solve problems independently or always need the help of a friend or teacher, many as 2 people. The research subjects had an average percentage of sociomatematic norms ˃ 56%, this means that these subjects had good mathematical communication skills and social skills.